2014
DOI: 10.5539/ijbm.v9n2p262
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Conflict: A Survey Study on the Public Institution for Social Insurance

Abstract: The aim of this study is to identify the causes of organizational conflict from the point of view of auditors working in the Public Institution for Social Insurance, and their relationship to role ambiguity, organizational climate, work pressures and the commitment of senior management to support and endorse the policies and decisions aimed at developing work and achieving the organizational objectives. A questionnaire has been designed for this purpose, and a suitable sample consisting of seventy-five partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Prior studies analyze that task-related conflict harm the self-respect of an individual and to protect their self-respect, individual reacts defensively and aggressively and thus, this type of defensive behavior activates hostility in others that generate relationship conflicts (Choi & Cho, 2011;De Wit et al, 2012). Almutairi and AL-Shammeri (2014) discussed the causes of OCs in the public institution (social insurance). The study shows that continuing the significant impact on work pressure, the commitment of senior management, and role ambiguity creates a high OC level.…”
Section: Mediating Effect Of Organizational Conflictmentioning
confidence: 99%
“…Prior studies analyze that task-related conflict harm the self-respect of an individual and to protect their self-respect, individual reacts defensively and aggressively and thus, this type of defensive behavior activates hostility in others that generate relationship conflicts (Choi & Cho, 2011;De Wit et al, 2012). Almutairi and AL-Shammeri (2014) discussed the causes of OCs in the public institution (social insurance). The study shows that continuing the significant impact on work pressure, the commitment of senior management, and role ambiguity creates a high OC level.…”
Section: Mediating Effect Of Organizational Conflictmentioning
confidence: 99%
“…Perez-Alvarez (2012) concluded that the effective adoption of technologies requires a fit between the features of the technology and the cultural aspects of the environment in which they will be used. According to Almutairi and AL-Shammeri (2014), culture plays a significant role in a manager's perception of new technology. This could be related to new technology meeting the needs and requirements of the individual.…”
Section: Culture and Technologymentioning
confidence: 99%